The practicalities of using tissue slices as preclinical organotypic breast cancer models. Issue 3 (16th October 2012) - Holliday, Deborah L; Moss, Marcus A; Pollock, Steven; Lane, Sally; Shaaban, Abeer M; Millican-Slater, Rebecca; Nash, Claire; Hanby, Andrew M; Speirs, Valerie
Abstract : Models considering breast cancer complexity cannot be easily or accurately replicated in routine cell line or animal models. We aimed to evaluate the practicality of organotypic tissue slice culture in breast cancer. Following ethical approval, 250 µm thick sections from surplus breast tumours (n=10) were prepared using a vibrating blade microtome. Triplicate tissue slices were placed in 6-well plates and cultured for up to 7 days±tamoxifen (1 nM) or doxorubicin (1 µM). Tissue slices were fixed and embedded before sectioning for morphological evaluation and immunohistochemistry. H&E showed good preservation of tissue morphology. Collagen production was evident. Biomarkers of proliferation and apoptosis could be evaluated using immunohistochemistry and used as surrogates to quantify drug effects. In summary, breast cancer tissue slices can be cultured in vitro as organotypic models. Nevertheless, although simple in concept, the delicacy of the model with regard to handling makes subsequent analytical processes challenging.